Validation of an analytical method for the determination of polycyclic aromatic hydrocarbons by high efficiency liquid chromatography in PM10 and PM2, 5 - Herrera-Murillo, Jorge (2012)
An analytical method for polycyclic aromatic hydrocarbons in PM10 and PM 2.5 par ticles collected from air by high performance liquid chromatography (HPLC) was validated. The PAHs analyzed in the methodology include: Naphthalene, Acenaphthylene, Fluorene, Acenaphthene, Phenanthrene, Anthracene, fluoranthene,pyrene,Benzo(a)anthracene,Chrysene, Benzo (b)fluoranthene, Benzo (k)fluoranthene, Benzo (a)pyrene Dibenzo (a, h)anthracene, Benzo (g, h, i)perylene and Indeno (1,2,3-CD)pyrene. For these compounds, the detection limit and quantification limit were between 0,02 and 0,1 mg/l using a DIONEX ICS 3000 model cromatograph, that has two in serie detectors: UV/Vis and Fluorescense, separating the different absorption and emission signals for proper identification of individual compounds. For all the compounds analyzed the recovery factor was not significantly different from each other and the repeatability and reproducibility was found to be suitable for an analytical method, especially for the lighter PAHs.